A case study of the adaptation of problem-based learning for programming subjects. (21st February 2011) - Alvarez Garcia, Victor Manuel; Paule Ruiz, Maria Del Puerto; Perez Perez, Juan Ramon; Martin Garcia, Manuel Antonio
This article describes a case study of the adaptation of the problem-based learning (PBL) method for a programming subject. For this study, we focused in a web programming subject which is part of the academic programme for the Computer Science degree at the University of Oviedo. Taking as base previous implementations of PBL by other universities, we propose a method adapted to programming learning. This article analyses pros and cons resulted from applying this method in the web programming course, as well as results obtained from the study, including comparative grade distribution and appreciations from lecturers and students.